ISLAMIZATION OF KNOWLEDGE OF ISMAIL RAJI AL-FARUQI IN TYPOLOGIES OF SCIENCE AND RELIGION - Sri Hariyati Lestari (TA'LIM : Jurnal Studi Pendidikan Islam, 2020)
This paper discusses the Islamization of knowledge according to Ismail Raji al-Faruqi. The description of the scientific background and historical intellectuality of al-Faruqi who later initiated to the idea of ​​Islamizing knowledge and science, its arguments, methods and ways of working, as well as the objectives to be achieved with the concept are described analytically. This paper concludes that Islamization of knowledge is positioned as filter group, dialogue and confirmation models in typology of science and religion. The Islamization of knowledge seeks to distill the sciences with Islamic values ​​as a filtering tool. It is also a form of dialogue typology between modern science and religious values. Moreover, it is also seen as a form of scientific confirmation of Islam. The way it works refers to the 5 (five) principles of monotheism or oneness (tawh|i>d), namely: the oneness of God, the unity of the universe, the unity of truth and the unity of knowledge, the unity of life and unity of mankind, with the belief that of all the final set of goals, wills and desires that are built by the estuary finally is God.